CREATE A COMPOSITION THAT REFLECTS THE SCENERY OF A WATERFALL - Ochildiyeva Ozoda (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides scientific information about the composition of the waterfall landscape. In addition, the role of various methods in visual representation was discussed.